Assessment of Genotoxicity of Citrobacter freundii Bacteriocin on Bone Marrow Cells in Albino Mice - Hammad, Rasha Noori; Obaid, Hind Hussein (Iraqi Journal of Science, 2020)
Genotoxic effects of crude bacteriocin extracted from Citrobacter freundii were detected on albino mice bone marrow cells in vivo, using micronucleus (MN) and comet assay. The mice were administered intraperitoneally with 37.5, 75, 150 and 300 mg/kg of the extract for 24 hours. C. freundii was isolated from patients suffering from urinary tract infections (UTI). The bacteriocin producing isolates were determined using cup assayand the most efficient bacteriocin producers were selected. Bacteriocin was extracted from the efficient isolates via the induction with Mitomycin-C (2 mg/ml). Bacteriocin activity (320 U/ml) was determined by well diffusion method, while the protein concentration (2900µg/ml) was estimated by Lowery method. The results showed an acute dose-dependent toxic effect of the crude bacteriocin ; The higher doses (150 and 300 mg/kg) caused a significant increase (P≤0.05) in the micronuclei frequency in the bone marrow cells (4.62 and 5.37%, respectively (. Furthermore, DNA damage increased significantly (P≤0.05) and proportionally to higher bacteriocin doses (75, 150 and 300 mg/kg), as demonstrated by increased values of tail length (145.18, 267.73 and 295.08 %,( %DNA in tail (8.05, 13.87 and 14.31 %(, and olive tail moment (13.25, 22.72 and 25.85 % , respectively.